STRATEGI PUBLIC RELATIONS RUMAH SAKIT CINTA KASIH TZU CHI DALAM EMPLOYEE RELATIONS - Suryani, Ita; Bakiyah, Horidatul; Indarsih, Mike; Efendi Dabukke, Rikardo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research entitled "Public Relations Strategy Hospitals Charity Tzu Chi In Employee Relations". Ineffective employee relations as well as services that are less good at the hospital Charity Tzu Chi will result in failure which can result in a negative impact against the hospital itself. The above problems will be solve by making an activity that is build and educate employees in order to always be able to work better in serving the patients and can be more compact in each process in the works. This research uses the scientific research method of characteristics are rational, empirical and systematic way. where in it include observation, interviews and so forth that serves to complete the research well and true. The data obtained in the research results of the Tzu Chi kegitan Camp that is add to it insights participants, add to the cohesiveness of the participants as well as the Committee's activities. The participants also willing when employee relations activities as has been done will be done again, because the participants admitted to obtain the many benefits that can be done in the workplace and in the environment. Tzu Chi Camp activity can be arranged well done and has a wonderful benefit. It seens from the employee who more diligent, compact andappreciate with the others. They keep environment well and keeping health with the vegetarian.